Persistent colonization of exit site is associated with modality failure in peritoneal dialysis. Issue 1 (January 2022) - Nadarajah, Luxme; Yaqoob, Muhammed M; Fan, Stanley
Exit-site infections (ESIs) increase the risk of developing peritoneal dialysis (PD) peritonitis and PD technique failure. There are no clear guidelines on how to monitor exit site (ES) after ESI with Staphylococcus aureus or Pseudomonas . We report on a 1-year observational study of 23 patients who developed an ESI with one of these serious pathogens. After completing initial antibiotic treatment, swabs were taken every month for 3 months. Primary treatment cure occurred in 19/23 (83%). Colonization of ES after primary cure occurred in 8/19 (42%) patients. In the eight colonized patients, five had subsequent PD technique failure due to infections. By contrast, during an average follow-up period of 7.2 months, none of the 11 patients who were proven noncolonized developed PD technique failure from infections; HR (colonized vs. noncolonized) = 10.89, 95% CI 2.6–45.43, p < 0.05. In conclusion, colonization significantly increased the risk of catheter loss. Increased surveillance and aggressive treatment may ameliorate this risk.